2016
DOI: 10.1007/s00702-016-1559-9
|View full text |Cite
|
Sign up to set email alerts
|

Ventral medial prefrontal cortex (vmPFC) as a target of the dorsolateral prefrontal modulation by transcranial direct current stimulation (tDCS) in drug addiction

Abstract: Here, we report some electrophysiologic and imaging effects of the transcranial direct current stimulation (tDCS) over the dorsolateral prefrontal cortex (dlPFC) in drug addiction, notably in alcohol and crack-cocaine dependence. The low resolution electromagnetic tomography (LORETA) analysis obtained through event-related potentials (ERPs) under drug-related cues, more specifically in its P3 segment (300-500 ms) in both, alcoholics and crack-cocaine users, showed that the ventral medial prefrontal cortex (vmP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 68 publications
0
41
0
Order By: Relevance
“…Previous human cross sectional studies (Moeller et al, 2005; 2007; Lim et al, 2002; 2008; Ma et al, 2009; 2015; Lane et al, 2010; Romero et al, 2010; Xu et al, 2010; Bell et al, 2011; Nakamura-Palacios, 2016) compared DTI measures between CocUD and controls at a single time point. Thus the white matter alterations found by these studies could be due to the combination of pre-existing factors and chronic cocaine use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous human cross sectional studies (Moeller et al, 2005; 2007; Lim et al, 2002; 2008; Ma et al, 2009; 2015; Lane et al, 2010; Romero et al, 2010; Xu et al, 2010; Bell et al, 2011; Nakamura-Palacios, 2016) compared DTI measures between CocUD and controls at a single time point. Thus the white matter alterations found by these studies could be due to the combination of pre-existing factors and chronic cocaine use.…”
Section: Discussionmentioning
confidence: 99%
“…Though there exist exceptions (e.g., Kelly et al, 2011), the majority of previous DTI studies (Moeller et al, 2005; 2007; Lim et al, 2002; 2008; Ma et al, 2009; 2015; Lane et al, 2010; Romero et al, 2010; Xu et al, 2010; Bell et al, 2011; Nakamura-Palacios, 2016; Yip et al, 2016) have reproducibly shown that cocaine use disorder (CocUD) is associated with white matter alterations, with consistent findings in the corpus callosum (Moeller et al, 2005; 2007; Ma et al, 2009; 2005; Lane et al, 2010; Xu et al, 2010; Bell et al, 2011). The white matter alterations found in CocUD may be related to impulsivity (Moeller et al, 2005), decision-making (Lane et al, 2010), treatment outcomes (Xu et al, 2010), or abstinence duration (Bell et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Right and left DLPFC are consistent with F4 and F3 based on the international 10-20 system of EEG electrode placement. A couple of studies reported promising findings in reducing subjective craving with this electrode montage (Boggio et al, , 2010Fecteau et al, 2014;Nakamura-Palacios et al, 2016). For the real DC stimulation, 2 mA current intensity was applied for 20 min including a 30-s ramp.…”
Section: Transcranial Direct Current Stimulationmentioning
confidence: 99%
“…In a more recent ERP study, Nakamura-Palcious et al reported increased P3 activation over the ventral medial prefrontal cortex (vmPFC) under drug-related cues in alcoholics and crack cocaine users during and after the treatment with bilateral tDCS over DLPFC. In crack cocaine users, they also K E Y W O R D S functional connectivity, large-scale brain networks, methamphetamine craving, noninvasive brain stimulation, resting state fMRI, transcranial direct current stimulation found increased diffusion tensor imaging (DTI) parameters relating to the connection between vmPFC and nucleus accumbens (NAcc); this increase was significantly correlated with craving decrease after repetitive tDCS (Nakamura-Palacios et al, 2016). However, these studies merely confirm the role of prefrontal cortex, but not network effects.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, repeated anodal tDCS over the left DLPFC could also effectively reduce craving and prevent relapse in alcoholics and methamphetamine abusers (da Silva et al, 2013; Shahbabaie et al, 2014; den Uyl et al, 2015), and decrease risky choices in cocaine addicts (Gorini et al, 2014). Nakamura-Palacios et al (2016). It is suggested that this cognitive improvement might be associated with ventromedial prefrontal cortex (VMPFC) activation as modulated by the DLPFC activity change that resulted from repetitive anodal tDCS.…”
Section: Tdcs Applications In Clinical Samplesmentioning
confidence: 99%